THE DYNAMICS OF TERRORISM AND COUNTER-TERRORISM: THE SOUTH AFRICA EXPERIENCE - Afowowe, Oluranti Samson (Journal of Terrorism Studies, 2025)
Defining Terrorism within the context of South African government promulgated Terrorism Act of 1967 as’ action(s) that endanger the maintenance of law and order’, innocuously suggest that the phenomenon of terrorism in South African political space is not a recent development. This study examines the historical, socio-economic and demographic dis-equilibrium as indicative factors of terrorism within the context of South Africa. Theoretical postulations on the phenomenon of terrorism within the context of South Africa state experience also engaged the attention of this study. Attempts are made to identify the nexus between social relationships and the nature, essence and political dimensions of terrorism in South Africa. Using the two classical theories on counter-insurgency (the enemy-centric approach and the population-centric approach theories), the relative efficacies of governmental institutional mechanisms for counter-terrorism in South Africa are also examined.